The Role of Daqu Bisnis Nusantara in Developing Economic Independence at Daarul Qur'an Islamic Boarding School - Dewi, Nur Diana; Setiyadi, Desi; Zaenurrosyid, A. (Mafapress - Lembaga Penelitian dan Pengabdian Masyarakat (LPPM) IPMAFA Pati, 2024)
Islamic boarding schools have great resource potential. According to Islamic Boarding Schools Database 2022, currently the number of santri has reached 4,009,547 people spread across 26,974 Islamic boarding schools throughout Indonesia. As a mandate from the Decree of the Minister of Religion Number 749 of 2021 concerning the Islamic Boarding School Independence Program, a road map needs to be prepared as a guide in implementing the Daarul Qur'an independence program, in the form of a road map for economic independence. In facing various challenges, Daarul Qur'an not only strives to form intellectually qualified individuals, but also understands the need for strong planning, management and economic development to maintain institutional stability and independence, thus creating Daqu Bisnis Nusantara. This research was conducted with the aim of analyzing the role of Daqu Bisnis Nusantara as a supporting factor for economic independence at Daarul Qur'an. This research uses a qualitative approach with analytical descriptive methods, interview techniques and Forum Group Discussion to obtain data sources. As an institution operating in the field of Islamic Education, Daarul Qur'an recognizes the importance of sustainable economic development to support Daarul Qur'an's vision and mission. Daqu Bisnis Nusantara has developed by Daarul Qur’an to achieve economic independence for business units.